Structure of a human gastrin gene. - Wiborg, O (1984)
A gastrin gene was isolated from a genomic library of human DNA. The human gastrin gene is about 4100 base pairs long and contains two intervening sequences. Thus, a 3500-base-pair intervening sequence is located 5 base pairs proximal to the ATG initiator codon, while a 129-base-pair intervening sequence separates the region coding for the principal hormonal form of gastrin, the heptadecapeptide, from the region coding for the major amino-terminal portion of the gastrin precursor. The 5' flanking region of the gene contains the conserved sequences, T-A-T-A-A and G-A-C-T-C-A-T-A-T, in positions similar to those of other eukaryotic genes.